Biomechanics Analysis some Variables Step Fife Hurdle of the Effectiveness of 110 Hurdles - Abedulrahman, Ayad (Journal of Physical Education, 2014)
The race (110 meters) barriers more races Athletics linked to performance motor technical complex so it is the most important races that determined the level of the level of motor performance in addition to the development level of the elements of fitness different and we can say that racing barriers need generally to the extent large fitness (strength, speed and flexibility) and higher technical performance. This study aims to identify some of the biomechanics variables step hurdle and force variables for the upgrading and landing phase of a sample of four applicants effectively players (110) hurdles before, during and after passing the hurdle for the fifth hurdle. Based on the results obtained through analysis biomechanics effectiveness (110 meters) hurdles and according to international law and put force platform under the hurdle and by (3 meters) before the barrier and (2 meters) after hurdle to cover the step hurdle full was obtained monuments statistically significant that determine performance good motor for the research sample. The analysis of the performance of technical research sample and hurdle only the fifth in chose them was conducted and the barriers of formal high (1,67 meters) and can be defined as the efficiency of cross barriers (hurdle step) through the horizontal speed of the center of gravity of the body during the upgrade hurdle, and height (center of gravity body) through upgrading, and upgrading angle, and flight time and minimize loss in the horizontal speed to less than what can be the center of gravity of the body, and reduce the contact time in the upgrading and landing phase after the landing. On the basis of the results obtained and through biomechanics analysis of the effectiveness of (110) meters hurdles was obtained important statistical parameters that determine the kinetic model ideal. The analysis of the performance of technical runners of the fife hurdle) in an experiment conducted on runners from a high level according to the principles important to pass the barriers is a variable-speed horizontal center of gravity body during upgrading of the hurdle, and height (center of gravity body) during the upgrade, and the angular velocity of the knee through the stage weighted and flight time and minimize loss in speed horizontal identified on the amount of the outcome of the power to the two phases of upgrading and landing using platform strength to step fifth hurdle and vertical velocity and the horizontal and time passing hurdle to less what can be the center of gravity of the body, and reduce the time contact l at the moment of landing after hurdle choose barrier fifth due to The runners under study was their top speed at the fifth hurdle